2000
DOI: 10.1093/ajcn/72.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum and milk-derived peptide growth factors for the treatment of gastrointestinal disorders

Abstract: Colostrum is the specific first diet of mammalian neonates and is rich in immunoglobulins, antimicrobial peptides, and growth factors. In this article we review some of these constituents of human and bovine colostrum in comparison with those of mature milk. Recent studies suggest that colostral fractions, or individual peptides present in colostrum, might be useful for the treatment of a wide variety of gastrointestinal conditions, including inflammatory bowel disease, nonsteroidal antiinflammatory drug-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
231
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(247 citation statements)
references
References 83 publications
8
231
0
8
Order By: Relevance
“…Of course, many other factors found in colostrum/milk are likely to be acting via a lactocrine mechanism to affect development of the uterus and other reproductive and somatic tissues. It is well known that steroid and peptide hormones, cytokines, and growth factors are present in colostrum/milk (Grosvenor et al 1993, Osterlundh et al 1998, Playford et al 2000, Salmon et al 2009). Recently, microRNAs, which can regulate gene expression by silencing translation (Alvarez-Garcia & Miska 2005), were identified in human and bovine milk (Hata et al 2010, Kosaka et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, many other factors found in colostrum/milk are likely to be acting via a lactocrine mechanism to affect development of the uterus and other reproductive and somatic tissues. It is well known that steroid and peptide hormones, cytokines, and growth factors are present in colostrum/milk (Grosvenor et al 1993, Osterlundh et al 1998, Playford et al 2000, Salmon et al 2009). Recently, microRNAs, which can regulate gene expression by silencing translation (Alvarez-Garcia & Miska 2005), were identified in human and bovine milk (Hata et al 2010, Kosaka et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in several species indicates that colostrum, the first milk secreted after birth in mammals, acts as a conduit for transmission of signaling molecules from mother to offspring (Ogra et al 1977, Simmen et al 1990, Grosvenor et al 1993, Playford et al 2000, Almeida et al 2008, Langer 2009). Defined as lactocrine signaling (Yan et al 2006b, neonatal consumption of bioactive factors in colostrum affects differentiation of anterior pituitary mammotropes (Nusser & Frawley 1997), gastrointestinal tract development (Shulman 1990, Donovan & Odle 1994, Burrin et al 1995, and immune system maturation (Lonnerdal 2003, Field 2005, Kosaka et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…After maturity, humans gradually lose the immune and growth factors in the body. Aging, illness and death occur with the loss of immune and growth factors in the human body which can possibly be replaced in the human body with bovine colostrum [1] [3]. Since colostrum is a natural food, it can be consumed without experiencing side effects or drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Colostrum is rich in immunoglobulins, antimicrobial peptides (lactoferrin and lactoperoxidase) and a number of other bioactive molecules and growth factors. 26 The protein content is very high (B11% v/v), and the whey proteins include a-lactalbumin, b-lactoglobulin, serum albumin, immunoglobulins, lactoferrin and peptide hormones such as growth hormone 27 and insulin-like growth factors, 28 epidermal growth factor, 29 betacellulin, 27 transforming growth factor b 30 and platelet-derived growth factor. 26 In cell-lines, animal models 31,32 and human studies, 33 such growth factors have shown potential for proliferation and differentiation of both immature and mature cells in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%